Wait until dark [videorecording (DVD)] - Young, Terence, 1915-1994; Hepburn, Audrey, 1929-1993; Arkin, Alan; Crenna, Richard, 1927-2003; Knott, Frederick (Warner Home Video, 2003)
A photographer unwittingly smuggles a doll stuffed with heroin into New York City. His recently blinded wife, alone in their apartment, is first terrorized by hired crooks, and then by the psychopathic Roat, in search of the doll.